2017
DOI: 10.1111/jfpp.13511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acid pretreatment on the physicochemical and antioxidant properties of germinated adlay ( Coix lachryma‐jobi L.)

Abstract: Germinated adlay has gained considerable research attentions due to its improved texture and larger amounts of secondary metabolites than raw adlay. This study aimed to investigate the effect of acids pretreatments on the physicochemical and antioxidant properties of germinated adlay. Germination whether with or without acid pretreatment showed no significant effect on the Fourier transform‐infrared spectra and X‐ray diffraction patterns. However, acid pretreatment lowered the degradation of adlay storage prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that germinated adlay seeds exhibit increased levels of free phenols and flavonoids, while bound phenols and flavonoids are significantly reduced after germination [ 43 ]. Furthermore, germinated adlay seeds treated with citric acid have shown a significant increase in phenol (18.3%) and flavonoid (17.0%) content, as well as antioxidant activity (39.1%) compared to the control [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that germinated adlay seeds exhibit increased levels of free phenols and flavonoids, while bound phenols and flavonoids are significantly reduced after germination [ 43 ]. Furthermore, germinated adlay seeds treated with citric acid have shown a significant increase in phenol (18.3%) and flavonoid (17.0%) content, as well as antioxidant activity (39.1%) compared to the control [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The functional roles of the ingredients must be exploited through products. The purpose of functional ingredient research is to make use of these ingredients ( 87 ). Initial research clarified the content and function of the ingredients, and then the functional components were developed for use ( 88 ).…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…FTIR spectroscopy measures the presence or absence of any specific functional group as well as molecular vibrations of their covalent bonds (Jan et al, 2017) O-H functional group and were found to be highest for 72 h GBSF ascribing to improved functional properties of BSF post germination (Adebiyi et al, 2016). The active absorption bands at 2918.35 and 2305.47 cm −1 were ascribed to the stretching vibration of symmetric and asymmetric C-H bond (Xu et al, 2018). Further, the peak intensity increased with increase in germination period attributing to the bound water present in the form of moisture (Adebiyi et al, 2016).…”
Section: Ftirmentioning
confidence: 99%